“Arbitrators, but not only that...”: The clergy in the magistrates’ book of the City of Płock between 1489 and 1517 - Graczyk, Waldemar (Saeculum Christianum. Pismo Historyczne, 2021)
Entries made in the Płock magistrates’ book between 1489 and 1517 mention a total of nineteen clergymen, who were primarily associated with the local church environment. Evident in these entries is the clergy’s involvement as arbitrators in legal disputes. They are also mentioned as executors of testaments or recipients of legacies, parties in deeds of sale, holders of deposits, and prudent stewards of church property. Entries in the Płock magistrates’ book involving the local clergy seem to indicate that that the representatives of the Catholic Church were greatly trusted and esteemed by the local community.